2021
DOI: 10.3389/fphy.2020.531662
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multiple Animal Scanning on Image Quality for the Sedecal SuperArgus2R Preclinical PET Scanner

Abstract: Background: Increased throughput in small animal preclinical studies using positron emission tomography leads to reduced costs and improved efficiency of experimental design, however the presence of multiple off-centre subjects, as opposed to a single centered one, may affect image quality in several ways.Methods: We evaluated the count rate performance using a NEMA scatter phantom. A Monte Carlo simulation of the system was validated against this dataset and used to simulate the count rate performance for dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, due to the size limitations of the bed holed, it was not possible to image animals larger than a mouse. In a more recent study by Efthimiou et al [ 35 ], the impact of scanning multiple animal on image quality was investigated. The authors found that imaging more the two animals simultaneously resulted in a loss of image quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the size limitations of the bed holed, it was not possible to image animals larger than a mouse. In a more recent study by Efthimiou et al [ 35 ], the impact of scanning multiple animal on image quality was investigated. The authors found that imaging more the two animals simultaneously resulted in a loss of image quality.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical positron emission tomography (PET) scanners with extended Field of View (FOV) offer the capability to image multiple animals simultaneously, leading to cost reduction and enhanced radiotracer efficiency [1,2]. Due to the fact that the animals may be placed far from the center of the field of view (FOV), uniform image resolution and general image quality across the FOV is paramount [3][4][5][6]. This work proposes an algorithm to improve the resolution uniformity of reconstructed images, enabling multianimal imaging.…”
Section: Introductionmentioning
confidence: 99%